2009 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting 2009
DOI: 10.1109/isbmsb.2009.5133805
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and characterization of IPTV user behavior

Abstract: Analysis and characterization of IPTV user behaviorYu, Geng; Westholm, Tord; Kihl, Maria; Sedano, Inigo; Aurelius, Andreas; Lagerstedt, Christina; Ödling, Per Published: 2009-01-01 Link to publication Citation for published version (APA): Yu, G., Westholm, T., Kihl, M., Sedano, I., Aurelius, A., Lagerstedt, C., & Ödling, P. (2009). Analysis and characterization of IPTV user behavior. Paper presented at IEEE Symposium on Broadband Multimedia Systems and Broadcasting, Bilbao, Spain.General rights Copyright an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Existing studies [13], [19], [25], [42], [43] measured and modeled users' watching time distribution in various live streaming systems. Their results, however, cannot be naturally generalized to VoD streaming systems, as users' watching behavior in live streaming systems is significantly different from that in VoD streaming systems.…”
Section: Measurement Of User Watching Time In Live Streaming Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies [13], [19], [25], [42], [43] measured and modeled users' watching time distribution in various live streaming systems. Their results, however, cannot be naturally generalized to VoD streaming systems, as users' watching behavior in live streaming systems is significantly different from that in VoD streaming systems.…”
Section: Measurement Of User Watching Time In Live Streaming Systemsmentioning
confidence: 99%
“…Some studies (e.g., [14]- [19]) found that users usually only watch a small portion of the full content of a video. They, however, failed to characterize the relation between watching finish ratio and video-related properties.…”
Section: E Measurement Of User Watching Time In Vod Systemsmentioning
confidence: 99%